ANALISIS SANITASI PRODUK RAKIK DI ULAKAN KABUPATEN PADANG PARIAMAN - Nia Fista; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
This research originated from the researchers' observations when conducting surveys and observations in Ulakan, Padang Pariaman Regency, the researchers saw that the sanitation of rakik products in Ulakan, Padang Pariaman Regency was not good, such as food that was not closed, and the complaints of visitors when buying food that was there. found to be rotten. This study aims to analyze the sanitation of Rakik products in Ulakan, Padang Pariaman Regency. This type of research is descriptive with qualitative data with a survey method. The object in this study is Rakik products in Ulakan, Padang Pariaman Regency with research respondents, namely rakik traders in Ulakan, Padang Regency, amounting to 3 people and visitors who come to buy rakik products in Ulakan. Padang Pariaman Regency consists of 5 people. The data collection technique is done by using the method of observation, interviews and documentation. The data analysis technique includes three flow of activities, namely: data reduction, data presentation and conclusion drawing. . The results show that the sanitation analysis of rakik products in Ulakan, Padang Pariaman Regency can be described from the indicators, 1) Cleanliness of processing / cooks, clean enough does not have special uniforms in food processing, such as aprons, masks, 2) cleanliness of food processing facilities. , a little dirty and does not have a drain, dirty water tubs and dumped on roads, trash cans are not clean and scattered, 3) Cleanliness in touching food, traders touch food directly, do not wear gloves, cans are placed carelessly, 4) Cleanliness in storing foodstuffs cooked, inadequate traders store food in a hammer or dietalase, and the food storage area is only cleaned if it is not regularly dirty, 5) Cleanliness of the process of moving cooked food is less clean, traders use the same barrel as a frying barrel, 6) Cleanliness of the food serving process and drinks talk to buyers and don't wear a mask Keywords: Sanitation Products Rakik